Mung bean sprout extract suppresses Monosodium Glutamate (MSG) effect on the reproductive hormones (FSH and Estrogen) in female Wistar rats - Widati Fatmaningrum; Woro Setia Ningtyas (Universitas Airlangga, 2019)
Objectives: The purpose of this study was to analyze the effects of mung bean sprout extracts on Follicle stimulating hormone (FSH) and estrogen hormone in female Wistar rats (Rattus norvegicus) exposed to monosodium glutamate (MSG). Materials and Methods: This true experimental study was conducted by using post-test only control group design in the laboratory for animal experimentation of Faculty of Veterinary Medicine - Airlangga University in which Wistar rats (Rattus norvegicus) aged 2 months weighing 150-200 grams were used in this experiment. The samples comprised of 5 rats distributed in each group, totaling 7 groups. I Control Group (P1) was provided with Aquades for 37 days; II (P2) was provided with Aquades for 7 days + MSG 0.03 mg/g of weight on day 8-37; III (P3) was provided with extract of mung bean sprouts 72mg/200g of weight on day 1-37 + MSG 0,03mg/g of weight; IV (P4) was provided with extract of mung bean sprouts 144mg/200g of weight on day 1-37 + MSG 0.03mg/g of weight; V (P5) was provided with Aquades for 7 days + MSG 0.7 mg/g of weight on day 8-37; VI (P6) was provided with extract of mung bean sprouts 72mg/200g of weight on day 1-37 + MSG 0.7mg/g of weight; VII (P7) was provided with extract of mung bean sprouts 144mg/200g of weight on day 1-37 + MSG 0.7mg/g of weight.Serum samples were taken for Follicle Stimulating Hormone (FSH) and Estrogen with ELISA method. Data analysis to test the differences between groups was done by using one way Anova statistical test. Results: MSG dosage 0,03mg/gBB or 0,7mg/g BB was significant difference in FSH (p = 0,011) and estrogen (p = 0,008). Conclusion: obtained from this research that giving green bean sprout extract influence to the level of FSH and estrogen hormone.